VOCATIONAL TEACHERS' PERCEPTIONS REGARDING THE USE OF L1 IN THE EFL CLASSROOM : A Case Study at a Public Vocational High School in Bandung, Indonesia - Widyasari, - (2018)
Despite huge support for the implementation of an English-only policy, in the classroom, EFL/ ESL teachers seem to still depend immensely on the use of L1 in their teaching practices. This study was conducted to investigate further the aforestated issue by exploring the perceptions and pedagogical functions of the use of L1 by EFL teachers at a public vocational high school in Bandung, Indonesia. Two certified EFL teachers were involved as participants of the study. This case study employed a qualitative research design by collecting the data through classroom observations and semi-structured interview. The data collected in this study were analyzed qualitatively. Findings reveal that both vocational teachers have positive perceptions toward L1 use in the EFL classroom in vocational high school context despite the different opinions on the ideal percentage of L1 use. The classroom observation data provide more detail information regarding two things including the discrepancy between participants' perceptions and their actual classroom teaching practices and the 'over-use' of L1 performed by teachers in their teaching practices. Both participants, based on the data from classroom observations used L1 for specific functions. There is a need to constantly remind vocational teachers of the urgency to use only judicious amount of L1 in EFL teaching through MGMP (English teacher forum). Since L1 need to be seen by EFL teachers as a supporting tool; its uses in the classroom should not dominate the use of English as the target language.